Question Banks: A Tool for Improving Higher Education Assessment Across National Resource Networks: The Polytechnic of Malawi Case Study - Chilivumbo, Chifundo (My University, 2015)
Question Banks are used to increase the access to quality material for assessing the students in institutions of higher learning. A good question bank which is in line with the learning orientated assessment framework, should facilitate the, learning orientated assessment tasks, developing evaluate expertise and aid in student engagement with some feedback. This paper seeks to create a solution that will allow for these properties to be streamlined by an information solution for higher institutions to be delivered over National resource networks, with one of the University of Malawi’s constituent colleges, the Polytechnic as a case study. This paper documents the work done with the Department of Mathematics and Statistics and Language and Communication in the Faculties of Applied Sciences and Education and Media Studies respectively. Information about the assessment creation and assessment artifact storage was gathered from these two departments through the study of existent literature, observation of processes and a self-administered questionnaire given to participants from the two departments. The first version of the software was created with work being done to improve the system to ensure it’s efficiently aids the assessment process. Although the current process is paper based the system tracks the process using an electronic solution with the aim to allow for an aid to creation and research of questions and possibly in the future for electronic delivery of assessments. The system also takes into account the issue of interoperability of the new system with the Universities existing systems that support Virtual Leaning and Student Information Management.
Keywords: Question-bank; Assessment-Moderation; Higher Education; Assessment Artifacts; Moderation; E-assessment